Prospective evaluation of a rapid immunochromogenic cassette test for the diagnosis of melioidosis in northeast Thailand. - Cheng, A; Peacock, S; Limmathurotsakul, D; Wongsuvan, G; Chierakul, W; Amornchai, P; Getchalarat, N; Chaowagul, W; White, N; Day, N; Wuthiekanun, V (2006)
A prospective study was performed to compare a rapid immunochromogenic cassette test (ICT) with the indirect haemagglutination assay (IHA) and clinical rules for the diagnosis of melioidosis in an endemic area. The sensitivity and specificity of the IgG ICT was 86% and 47%, and the IgM ICT was 82% and 47%, respectively. These were similar to the results for IHA (sensitivity 73%, specificity 64%) and clinical rules (73% and 37%). ICT lacks clinical utility as a result of high background rates of positive Burkholderia pseudomallei serology in this population. Low sensitivity and specificity of clinical rules is consistent with the protean manifestations of melioidosis and clinical difficulty in identifying patients with melioidosis.